(untitled) - Tillery, Bill W. (Boston, 2007)
Integrated Science, Third Edition is a straightforward, easy-to-read, yet substantial introduction to the fundamental behavior of matter and energy in living and nonliving systems. The authors provide even, well-integrated coverage of chemistry, physics, earth science, biology, and astronomy. The book is intended to serve the needs of non-science majors who are required to complete one or more science courses as part of a general or basic studies requirement. This edition continues to introduce basic concepts and key ideas while providing opportunities for students to learn reasoning skills and a new way of thinking about their environment. No prior work in science is assumed. The language, as well as the mathematics, is as simple as can be practical for a college-level science course.
Keywords: Science; Textbooks